Dysplastic Progression to Adenocarcinoma is Equivalent in Ulcerative Colitis and Crohn's Disease. (27th July 2020) - Lightner, Amy L; Vogler, Sarah; McMichael, John; Jia, Xue; Regueiro, Miguel; Qazi, Taha; Steele, Scott R
Abstract: Background: We sought to determine the rate of progression from dysplasia to adenocarcinoma in ulcerative colitis [UC] vs Crohn's diseases [CD] and describe the risk factors unique to each. Methods: All adult patients [≥18 years] with a known diagnosis of either UC or CD who underwent a surveillance colonoscopy between January 1, 2010 and January 1, 2020 were included. Results: A total of 23 751 surveillance colonoscopies were performed among 12 289 patients between January 1, 2010 and January 1, 2020; 6909 [56.2%] had a diagnosis of CD and 5380 [43.8%] had a diagnosis of UC. There were a total of 668 patients [5.4%] with low-grade dysplasia [LGD], 76 patients [0.62%] with high-grade dysplasia [HGD], and 68 patients [0.55%] with adenocarcinoma in the series; the majority of the dysplastic events were located in the right colon. Significantly more UC patients had a dysplastic event, but the rate of LGD and HGD dysplasia progression to adenocarcinoma was not significantly different in CD or UC [ p = 0.682 and p = 1.0, respectively]. There was no significant difference in the rate of progression from LGD/HGD to adenocarcinoma based on random biopsies vs targeted biopsies of visible lesions [ p = 0.37]. However, the rate of progression from LGD vs HGD to adenocarcinoma was significantly greater for HGD [ p < 0.001]. Conclusion: While more UC patients were found to have neoplasia on colonoscopy, the rate of progression from LGD and HGD to adenocarcinoma was equivalent in UC and CD, suggesting that endoscopic surveillance strategies can remain consistent for all IBD patients.